The effectiveness of floor finishes in shopping centers / Elis Suzana Muhamad - Muhamad, Elis Suzana (2001)
Parts of dissertation include effectiveness of floor finishes in shopping centers. The study is about the usage of floor finishes system especially in shopping retails and its effectiveness to increase the standard of floor finishes. The effectiveness of floor finishes will be determined by consider to comfortability and appearance, durability, safety of floor and the floor maintenance. Most users / occupants are unaware of the importance of floor finishes especially to floor in building works, on the practical use and functions. In this context, the study focuses on the effectiveness of floor finishes. The general factors that determine materials and finishes of floor are the image it conveys the practical considerations and cost. This dissertation it will cover the aspect of material’s physical properties, problems involve in floors and factors influent the choice of floor finishes. The choice of floor is much important to determine the visual character of buildings. Floor finishes used in Shopping Center are categorized by the basic space defining elements. It covers the architectural and mechanical responses to indoor floor environment. Furthermore, the type of floor finishes will be the major criteria in shopping design and how it will effect the character and function of the space involved.